Food Insecurity: A Constant Factor in the Lives of Low-Income Families in Scotland and England - Shinwell, Jackie; Defeyter, Margaret Anne (Frontiers in Public Health, 2021)
During the school summer holidays, pressures on the already tight budgets of low-income families are compounded, particularly when the safety net of free school meals is removed. The main aim of the current study was to investigate how low-income parents and carers feed their families during term time when children receive free school meals and if, and how, strategies differ during the school summer holidays. A secondary aim was to investigate the role of holiday activity and food programmes in supporting parents and carers to feed their children during the school summer holidays. We used purposive sampling to recruit a total of 21 parents (N = 20 Female, N = 1 Male) whose children attended free summer holiday clubs in Scotland and England during summer 2017. Participants were asked about their food and shopping habits during the school term and if, and how they differed during the school summer holidays when free school meals were not available. The findings suggest that food insecurity is a constant factor in the lives of low-income parents in England and Scotland, and that the stages of food insecurity and the strategies employed to mitigate its effects appear to be cyclical, aligning with the Food and Agriculture Organisation's (FAO) food insecurity continuum and the school academic year. During term time, parents and carers worried about food, suggesting they were experiencing mild food insecurity, despite their children being in receipt of free school meals. As the school holidays approached, moderate food insecurity was experienced as parents reported that they began “provisioning,” storing food and reducing household expenditure. During the summer holidays, food did not last, and parental food acquisition habits became more intense. Parents downgraded food brands and bought reduced price items of food. Ultimately, parents self-sacrificed their own nutritional intake by only buying food their children would eat and parents often skipped meals or only ate their children's leftovers. However, children's attendance at holiday club helped make the food at home last longer and once school resumed, parents returned to their less intense, but constantly coping approach to food shopping. The findings of this study suggest that food insecurity is a constant factor in the lives of low-income families who simply do not have enough household income to prevent them from experiencing food insecurity, even when initiatives such as free school meals and access to holiday club provision with food and activities are in place.